Yolk sac tumor, a rare and challenging ovarian malignancy: case report - Ara, Anjum; Kumari, Kanika; Rani, Sushma; Chawla, Indu; Ahuja, Arvind; Phulware, Ravi H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Yolk sac tumors (YST) are rare and rapidly developing neoplasm presenting in young females. They are second most common germ cell tumor after dysgerminomas. Fertility preservation is an important concern in treatment of patients of YST. We present a case of 22 years nulliparous female with rapidly evolving abdominal mass. The patient underwent fertility preserving surgery with four cycles of post operative bleomycin etoposide and paclitaxel (BEP) chemotherapy and is fairly doing well. BEP chemotherapy has successfully improved the treatment outcomes of YST patients.